2008
DOI: 10.1346/ccmn.2008.0560105
|View full text |Cite
|
Sign up to set email alerts
|

The viscosity of organic liquid suspensions of trimethyldococylammonium-montmorillonite complexes

Abstract: An organophilic bentonite was prepared by means of a reaction of natural Na-montmorillonite with trimethyldococylammonium which has an especially long n-alkyl chain. The addition of trimethyldococylammonium to montmorillonite was in the range 0.25–3.0 times the cation exchange capacity (CEC) of the clay (i.e. 0.23–2.82 mmol/g clay). The particle morphology in organic liquid suspensions of organoclay complexes was studied by measuring the viscosity based on Eyring’s rate process and Robinson’s relative sediment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…Then, above the threshold temperature, particle associations might undergo an increase in the effective volume. Thus, an increase in volume fraction leads to an increase in yield stress value, as has been observed by other authors for clay suspensions (Minase et al, 2008). Interestingly, this particular behaviour has been recently reported by Wu et al (2012), who also suggested an increase in the effective volume fraction with increasing temperature for particulate dispersion in non-aqueous media.…”
Section: Effect Of Temperature At Atmospheric Pressuresupporting
confidence: 82%
“…Then, above the threshold temperature, particle associations might undergo an increase in the effective volume. Thus, an increase in volume fraction leads to an increase in yield stress value, as has been observed by other authors for clay suspensions (Minase et al, 2008). Interestingly, this particular behaviour has been recently reported by Wu et al (2012), who also suggested an increase in the effective volume fraction with increasing temperature for particulate dispersion in non-aqueous media.…”
Section: Effect Of Temperature At Atmospheric Pressuresupporting
confidence: 82%
“…In rubber or plastic materials, OMt not only is required to have good dispersion and peeling properties but also needs good heat resistance to meet the processability requirements [6]. Excellent thermal stability and good rheological properties are indispensable for the wide use of OMt in oil-based drilling fluid [7,8]. Therefore, it is desirable to prepare advanced OMt with controllable surface polarity, excellent thermal stability, good dispersion, and peeling properties.…”
Section: Introductionmentioning
confidence: 99%
“…Organoclay addition to a solvent leads to the formation of a gel-like microstructure, which depends on the characteristics of the interchangeable organic ions, the nature of the solvent, as well as the interactions between organoclay and solvent [5,6]. The resulting microstructure, formed as a consequence of the swelling capacity of organoclays in non-aqueous media, may result in shear-thinning characteristics and viscoplasticity, even at low clay concentrations [7][8][9]. Generally, these rheological properties are desirable in drilling fluids, as has been pointed out elsewhere [10].…”
Section: Introductionmentioning
confidence: 99%